2016
DOI: 10.1016/j.brat.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcome for mental disorders by enhancing memory for treatment

Abstract: Summary Patients exhibit poor memory for treatment. A novel Memory Support Intervention, derived from basic science in cognitive psychology and education, is tested with the goal of improving patient memory for treatment and treatment outcome. Adults with major depressive disorder (MDD) were randomized to 14 sessions of cognitive therapy (CT)+Memory Support (n = 25) or CT-as-usual (CTMS; n = 23). Outcomes were assessed at baseline, post-treatment and 6 months later. Memory support was greater in CT+Memory Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 79 publications
6
67
0
2
Order By: Relevance
“…Written informed consent was obtained and all participants gave this consent willingly. Details of the study are reported elsewhere (Harvey et al, 2016). Table 1 presents the demographic variables of the sample.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Written informed consent was obtained and all participants gave this consent willingly. Details of the study are reported elsewhere (Harvey et al, 2016). Table 1 presents the demographic variables of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a recent pilot randomized controlled trial (RCT) provided initial evidence supporting the use of Memory Support Intervention (MSI) as an adjunctive treatment to enhance patients’ memory for treatment and to improve treatment outcome in the context of cognitive therapy (CT) for depression (Harvey et al, 2016). The current version of the MSI is comprised of eight memory support (MS) strategies, including attention recruitment, categorization, evaluation, application, repetition, practice remembering, cue-based reminders, and praise recall (for more detail see Supplemental Material A).…”
mentioning
confidence: 99%
See 3 more Smart Citations